2020
DOI: 10.1101/2020.06.23.20138289
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal immunological analyses reveal inflammatory misfiring in severe COVID-19 patients

Abstract: Recent studies have provided insights into the pathogenesis of coronavirus disease 2019 (COVID-19)1-4. Yet, longitudinal immunological correlates of disease outcome remain unclear. Here, we serially analysed immune responses in 113 COVID-19 patients with moderate (non-ICU) and severe (ICU) disease. Immune profiling revealed an overall increase in innate cell lineages with a concomitant reduction in T cell number. We identify an association between early, elevated cytokines and worse disease outcomes. Followi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 39 publications
7
42
0
Order By: Relevance
“…Indeed, there are a number of clinical trials focused on the use of interferon and anti-inflammatory agents to counteract the sometimes deleterious immune response to SARS-CoV-2 infection (Angka et al, 2020). Such an approach could be key in treating severe cases of COVID-19, which correlate with cytokine storm and hyper-activation of immune responses normally not related to viral infections, particularly type-2 effectors (Lucas et al 2020). However, indiscriminate tempering of immune signaling would be counterproductive in the early stages of the infection and for patients with moderate disease, who appear to maintain a functional, well-adapted immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there are a number of clinical trials focused on the use of interferon and anti-inflammatory agents to counteract the sometimes deleterious immune response to SARS-CoV-2 infection (Angka et al, 2020). Such an approach could be key in treating severe cases of COVID-19, which correlate with cytokine storm and hyper-activation of immune responses normally not related to viral infections, particularly type-2 effectors (Lucas et al 2020). However, indiscriminate tempering of immune signaling would be counterproductive in the early stages of the infection and for patients with moderate disease, who appear to maintain a functional, well-adapted immune response.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, the D614G mutation, which increases virulence, has been reported as potentially increasing glycosylation at neighboring asparagine 616 (Brufsky and Lotze, 2020;Jia et al, 2020;Korber et al, 2020). A recent proteomic profiling study pointed to DC-SIGN as a mediator of genetic risk in COVID-19 (Katz et al, 2020) and finally it is of note that DC/L-SIGN expression is induced by proinflammatory cytokines such as IL-4, IL-6, IL-10 and IL-13, known to be overexpressed in severe SARS and COVID-19 cases (Lucas et al, 2020;Relloso and Puig-Kroger). These observations prompted us to investigate the potential interaction of C-type lectins receptors, notably DC/L-SIGN with SARS-CoV-2, through glycan recognition of the spike envelope glycoprotein, as well at their potential role in SARS-CoV-2 transmission.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that differential expression in distinct cell types may account for the disparity of Egr-1 and its target gene expression in healthy controls and COVID-19 patients. Longitudinal studies in COVID-19 patients revealed that cytokines and chemokines were dramatically elevated in the lungs and correlated with the severity of the disease(57). Egr-1 mRNA levels were elevated and correlated with TNFSF10/TRAIL expression in the adult but not developing neutrophils of the peripheral blood mononuclear cells of COVID-19 patients compared with healthy controls(Figure 15).…”
mentioning
confidence: 98%
“…(15,63,64). Recent studies have demonstrated dramatic changes in type I interferon, TNF-α, and IL-1 β production by immune cells and cytokine-mediated lung inflammation in COVID-19 patients(30,57,65,66). However, the role of Egr-1 in innate immunity and antiviral response to respiratory viruses in general and SARS-CoV-2, in particular, remains to be investigated.Transcriptional factor profiling in the transcriptome revealed that Egr-1was induced by IFN-α/β , TLR ligands, and TNF-α in human and mouse cells.…”
mentioning
confidence: 99%
“…Development of Th1-polarized responses is also a feature of SARS-CoV2 in humans 13 . Moreover, severe COVID-19 is accompanied by prolonged and exacerbated Th1 responses 14 , which are suspected to contribute towards the observed pathogenic hyper-inflammation. We therefore focused our analyses of the scRNAseq datasets on CD4 + T cells.…”
mentioning
confidence: 99%